Serological evidence for chikungunya and Zika virus infections in patients clinically diagnosed as dengue in Northern Sri Lanka - S. Briyangari; J. Kowsalavani; K. Murugananthan; F. Noordeen (Sri Lankan Journal of Infectious Diseases, 2023)
Background: Chikungunya (CHIKV), Zika (ZV) and dengue (DENV) viruses are transmitted by Aedes mosquitoes. CHIKV, ZV and DENV infections produce similar clinical features during the early phase of the illness. Disappearance of chikungunya for the last four decades and no reported evidence of Zika fever in Sri Lanka results in the diagnosis of any illnesses resembling dengue as DENV infection in the country.